Case Report: Spinal Stabilization Surgery Using a Novel Custom-Made Titanium Fixation System for the Spinal Instability Caused by Vertebral Malformation in a Dog - Kimura, Shintaro; Nakata, Kohei; Nakano, Yukiko; Nozue, Yuta; Konno, Naoyuki; Sugawara, Taku; Maeda, Sadatoshi; Kamishina, Hiroaki (Frontiers in Veterinary Science, 2021)
A 2-year-old Maltese was presented with wobbly gait of the pelvic limbs. Based on imaging examinations, a diagnosis of congenital malformation at T5-T8 and severe kyphosis causing spinal cord compression at T6-T7 was made. Dorsal laminectomy and stabilization of T6 and T7 vertebrae were performed. As the size of the vertebrae was small and they were severely deformed, novel custom-made titanium implants were used for spinal stabilization. Clinical signs were resolved 2 weeks after surgery. Although radiographic examination 373 days after surgery showed slight loosening of implants, postoperative course remained uneventful. This report describes the use of novel custom-made titanium implants for spinal fixation surgery in a dog.